Calculus

If f(x) = sqrt x + 3/sqrt x, then f’(4) =

  1. 👍
  2. 👎
  3. 👁
  1. since √x = x^(1/2)
    f(x) = x^(1/2) + 3x^(-1/2)
    f'(x) = 1/2 x^(-1/2) - 3/2 x^(-3/2)
    and plugging in x=4, that is
    f'(4) = (1/2)(1/2) - (3/2)(1/8) = 1/16

    1. 👍
    2. 👎
    👤
    oobleck
  2. 4√a-3=10

    1. 👍
    2. 👎

Respond to this Question

First Name

Your Response

Similar Questions

  1. algebra

    Simplify: 2 sqrt (3) + 6 sqrt(2) - 4 sqrt(3) + sqrt (2) a) 8 sqrt(2) - 3 sqrt(3) b) 6 sqrt(2) - 8 sqrt(3) c) 5 sqrt(6) d) 7 sqrt(2) - 2 sqrt(3) the answer i picked was d

  2. algebra

    Simplify: sqrt (21) (sqrt(7) + sqrt(3)) a) 7 sqrt (3) + 3 sqrt(7) b) 7 sqrt(3) + sqrt (3) c) sqrt (210) d) sqrt (147) + sqrt (63)''. a

  3. math;)

    Find the unit vector in the direction of u=(-3,2). Write your answer as a linear combination of the standard unit vectors i and j. a. u=-3[sqrt(13)/13]i+2[sqrt(13)/13]j b. u=-3[sqrt(5)/5]i+2[sqrt(5)/5]j c.

  4. algebra

    what is the simplified form of 3 sqrt (5c) x sqrt (15c^3) choices are a. 15c^2 sqrt (3) b.6c^2 sqrt (5) c. 5c^2 sqrt(3) d. 12c^4 sqrt(5) please help i don't understand how to do the question i would really appreciate it

  1. is this correct?- math

    find the domain of the real valued function; f(x) = sqrt(5 - (sqrtx)) my solution: 5 - (sqrt x) >=0 -(sqrt x) >= -5 (sqrt x)

  2. algebra

    simplify: square root of 5 + square root of 20 - square root of 27 + square root of 147. simplify: 6/4square root of 2 sqrt 5 + sqrt 20 - sqrt 27 + sqrt 147 = sqrt 5 + sqrt (4*5) - sqrt (3*9) + sqrt (49*3) = 3 sqrt 5 - 3 sqrt 3 +

  3. Algebra

    Evaluate sqrt7x (sqrt x-7 sqrt7) Show your work. sqrt(7)*sqrt(x)-sqrt(7)*7*sqrt(7) sqrt(7*x)-7*sqrt(7*7) sqrt(7x)-7*sqrt(7^2) x*sqrt 7x-49*x ^^^ would this be my final answer?

  4. algebra

    Simplify -11 sqrt 112. -44 sqrt 7******** -176 sqrt 7 -27 sqrt 7 4 sqrt 7 Is this right? and I need to show my work, idk the steps

  1. algebra

    am I right? 1. Simplify radical expression sqrt 50 5 sqrt ^2*** 2 sqrt ^5 5 sqrt ^10 5 2. Simplify the radical expression sqrt 56x^2 28x 2x sqrt 14*** 2x sqrt 7 sqrt 14x2 3. Simplify the radical expression. sqrt 490y^5w^6 2 sqrt

  2. Algebra

    Which of these expressions is in simplified form? A. a ^3 sqrt 4 - b ^3 sqrt 2 / 2 B. sqrt 1/2x + sqrt 1/2z C. x^2 - 3x sqrt y / sqrt 3 D. sqrt 125x - x^2

  3. Calculus - Second Order Differential Equations

    Solve the initial-value problem. y'' + 4y' + 6y = 0 , y(0) = 2 , y'(0) = 4 r^2+4r+6=0, r=(16 +/- Sqrt(4^2-4(1)(6)))/2(1) r=(16 +/- Sqrt(-8)) r=8 +/- Sqrt(2)*i, alpha=8, Beta=Sqrt(2) y(0)=2, e^(8*0)*(c1*cos(0)+c2*sin(0))=c2=2

  4. Calculus

    show lim x->3 (sqrt(x)) = (sqrt(c)) hint: 0< |sqrt(x)-sqrt(c)|= (|x-c|)/(sqrt(x)+sqrt(c))

You can view more similar questions or ask a new question.